Penguatan Komunikasi Efektif Guru dalam Proses Pembelajaran di SMK Taruna Persada Dumai - Sugeng Purwantoro E.S.G.S; Memen Akbar; Kartina Diah Kusuma Wardhani; Mardhiah Fadhli; Yuli Fitrisia (Universitas Lancang Kuning, 2022)
One of the initial approaches to make learning more enjoyable is to know the patterns of social interaction and types of student communication. There are 3 types of social interaction patterns presented in this training, namely interactions between individuals who wish to achieve achievement (Achievement), desire to socialize with their social environment (Affiliation), and desire to power (Power). Teachers can communicate effectively with students if the teacher knows the type of communication used by students. There are 4 types of individual communication types with their environment. Some communicate concretely, spontaneously, intellectually, and sensitively. Community Service activities carried out are training for teachers to recognize the types of student social interactions and types of student communication. The training was carried out by introducing the two instruments that had been made. The training was held for 1 day offline at SMK Taruna Persada Dumai. Based on the feedback provided by the participants, the teacher felt the benefits of the training and was willing to apply the results of the training to students in the classroom.